2001
DOI: 10.1002/job.105
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of basic versus career enrichment benefit satisfaction

Abstract: SummaryUsing a sample of 250 medical technologists (MTs) over a four-year time period, this study presents initial evidence for differentiating two different facets of bene®t satisfactionÐbasic and career enrichment. Basic bene®t satisfaction exhibited stronger relationships to subsequent general bene®t satisfaction, organizational withdrawal intent, and turnover behavior, while career enrichment bene®t satisfaction exhibited a stronger relationship to subsequent affective organizational commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Findings from the academic arena are inconclusive as well. Although some researchers have found a strong, positive relationship between POS and desired employee outcomes (Babakus et al, 1996;Eisenberger et al, 1990;Randall et al, 1999;Whitener, 2001), others have found the relationship to be weak (e.g., Blau et al, 2001;Coyle-Shapiro and Kessler, 2000;Stinglhamber and Vandenberghe, 2003), or even negative (e.g., Cropanzano et al, 1997;Masterson et al, 2000). Conflicting findings such as these are problematic considering the resources firms are investing in these programs, and highlight the need for clarification.…”
Section: Introduction and Study Developmentmentioning
confidence: 85%
“…Findings from the academic arena are inconclusive as well. Although some researchers have found a strong, positive relationship between POS and desired employee outcomes (Babakus et al, 1996;Eisenberger et al, 1990;Randall et al, 1999;Whitener, 2001), others have found the relationship to be weak (e.g., Blau et al, 2001;Coyle-Shapiro and Kessler, 2000;Stinglhamber and Vandenberghe, 2003), or even negative (e.g., Cropanzano et al, 1997;Masterson et al, 2000). Conflicting findings such as these are problematic considering the resources firms are investing in these programs, and highlight the need for clarification.…”
Section: Introduction and Study Developmentmentioning
confidence: 85%
“…Also, Gellatly, Hunter, Currie and Irving (2009) posited a significant relationship between firms compensation packages and employees affective and continuance commitment towards their organization. Likewise, Blau, Merriman, Tatum and Rudmann (2001) reported a significant relationship between performance based compensation and organizational commitment. In contrast, in the studies of Fiorito, Bozeman, Young and Meurs (2007) it became evident that performance based compensation are negatively related to organizational commitment.…”
Section: Performance Based Pay and Organizational Commitmentmentioning
confidence: 95%
“…Noe et al ., 1997). In fact, research has shown that employee satisfaction with development opportunities in general is related to organisational commitment (Meyer and Smith, 2000; Bartlett, 2001; Blau et al ., 2001; Tansky and Cohen, 2001).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%